Respuesta :

Answer:

  • y = 3(x - 2)² - 5

==================

Given equation

  • y = 3x² - 12x + 7

Convert this to vertex form

  • y = a(x - h)² + k

Follow the steps

y = 3x² - 12x + 7 =

     3(x² - 4x) + 7 =                                  Factor out 3

     3(x² - 4x + 4) - 3*4 + 7 =                   Complete the square

     3(x - 2)² - 5                                       Simplify

Answer:

  y = 3(x -2)² -5

Step-by-step explanation:

It looks like you want to write the standard-form quadratic ...

  y = 3x² -12x +7

in vertex form.

The process is similar to that of "completing the square."

Steps

Factor out the leading coefficient

Do this for the variable terms only.

  y = 3(x² -4x) +7

Identify the x-term coefficient

The x-term coefficient (inside parentheses) divided by 2 is the opposite of the x-coordinate of the vertex. It is the constant term in the squared binomial of the vertex form. Square this value.

  x coefficient: -4

  binomial constant: -4/2 = -2

  square of this: (-2)² = 4

Add this inside parentheses

To keep the overall equation unchanged, you must also subtract an equal amount outside parentheses.

  y = 3(x² -4x +4) +7 -3(4)

Simplify to vertex form

Write the trinomial in parentheses as a square, and simplify the y-coordinate of the vertex.

  y = 3(x -2)² -5

ACCESS MORE